Serum AFU, 5’-NT and AFP as biomarkers for primary hepatocellular carcinoma diagnosis - Junna Zhu (Open Medicine, 2017)
To evaluate the clinical value of serum α-L-fucosidase (AFU), 5’-nucleotidase (5’-NT) and alpha fetoprotein (AFP) as biomarkers for primary hepatocellular carcinoma (PHC) diagnosis. Methods: Thirty six primary hepatocellular carcinoma (PHC) patients and 36 healthy controls were recruited in this study from February 2014 to January 2016 in the Second People’s Hospital of Tianjin. The serum level of AFU, 5’-NT and AFP were examined and compared between the two groups. The diagnostic sensitivity, specificity area under the receiver operating characteristic (ROC) curve were calculated by STATA11.0 software. Results: The serum level of AFU, 5’-NT, AFP were 30.87±10.43(U/L), 5.58±3.89(U/L), 233.60±226.60 (μg/L) respectively for primary hepatocellular carcinoma group and 19.96±6.73 (U/L), 1.87±0.84 (U/L), 16.64±14.17 (μg/L) for healthy control groups. The serum level of AFU, 5’-NT and AFP in primary hepatocellular carcinoma group were significant higher than those of healthy control group (P<0.001). The diagnostic sensitivity and specificity were 0.78 (95%CI:l0.61-0.90), 0.64 (95%CI:0.46-0.79) for serum AFU, 0.75(95%CI:0.58-0.88), 0.72(95%CI:0.55- 0.86) for serum 5’-NT and 0.72 (95%CI:0.55-0.86), 0.92 (95%CI:0.78-0.98) for serum AFP respectively. The AUC under the ROC curve were 0.80 (0.69-0.90), 0.80 (0.69-0.91) and 0.87 (0.780-0.96) for serum AFU, 5’-NT and AFP respectively. Positive correlation between AFU and 5’-NT (rpearson=0.63, P<0.05), AFU and AFP (rpearson=0.49, P<0.05), 5’-NT and AFP(rpearson=0.44, P<0.05) were found in the primary hepatocellular carcinoma patients. Conclusion: Serum AFU, 5’-NT and AFP were higher in PHC patients than those of healthy controls. The difference between PHC patients and healthy controls made serum AFU, 5’-NT and AFP potential biomarker for PHC diagnosis.